Environmental factors and risk of aggressive prostate cancer among a population of New Zealand men – a genotypic approach. Issue 4 (2nd March 2017) - Vaidyanathan, Venkatesh; Naidu, Vijay; Kao, Chi Hsiu-Juei; Karunasinghe, Nishi; Bishop, Karen S.; Wang, Alice; Pallati, Radha; Shepherd, Phillip; Masters, Jonathan; Zhu, Shuotun; Goudie, Megan; Krishnan, Mohanraj; et al.
Abstract : Genes with SNPs that were significantly associated with risk for aggressive and non-aggressive prostate cancer were identified. Abstract : Prostate cancer is one of the most significant health concerns for men worldwide. Numerous researchers carrying out molecular diagnostics have indicated that genetic interactions with biological and behavioral factors play an important role in the overall risk and prognosis of this disease. Single nucleotide polymorphisms (SNPs) are increasingly becoming strong biomarker candidates to identify susceptibility to prostate cancer. We carried out a gene × environment interaction analysis linked to aggressive and non-aggressive prostate cancer (PCa) with a number of SNPs. By using this method, we identified the susceptible alleles in a New Zealand population, and examined the interaction with environmental factors. We have identified a number of SNPs that have risk associations both with and without environmental interaction. The results indicate that certain SNPs are associated with disease vulnerability based on behavioral factors. The list of genes with SNPs identified as being associated with the risk of PCa in a New Zealand population is provided in the graphical abstract.